2003
DOI: 10.1002/app.11792
|View full text |Cite
|
Sign up to set email alerts
|

Continuous polymerization of lactam–lactone block copolymers in a twin‐screw extruder

Abstract: Continuous copolymerizations of ⑀-caprolactone with ⑀-caprolactam and -lauryl lactam were carried out in a modular intermeshing corotating twin-screw extruder. Sodium hydride (initiator) and N-acetyl caprolactam (coinitiator) were used to synthesize lactam-lactone copolymers in a twin-screw extruder. We consider the variables of feeding order and feed rate of comonomers on the reactive extrusion of lactam-lactone copolymers. It was observed that simultaneous feeding of both monomers with initiator and coinitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The structures of the diisocyanate PCLOs and PVLO derivates were confirmed by the 1 spectra in CDCl 3 solution. The broad doublet at 3.6 ppm assigned to the OH protons from hydroxyl and carboxyl end-groups of PVLO or hydroxyl groups of the PCLO polyol disappeared after the functionalization, as mentioned above.…”
Section: Synthesis Of Macroactivators On the Basis Pclo And Pvlomentioning
confidence: 80%
See 1 more Smart Citation
“…The structures of the diisocyanate PCLOs and PVLO derivates were confirmed by the 1 spectra in CDCl 3 solution. The broad doublet at 3.6 ppm assigned to the OH protons from hydroxyl and carboxyl end-groups of PVLO or hydroxyl groups of the PCLO polyol disappeared after the functionalization, as mentioned above.…”
Section: Synthesis Of Macroactivators On the Basis Pclo And Pvlomentioning
confidence: 80%
“…4a and b). The copolymerization reactions were also examined by 1 H NMR and FTIR analyses of the fractions extractable in chloroform, which established that only residual CLA monomer and oligomers were present. In the first stage of the polymerization, there was a depletion of the MA and then the copolymer becomes richer in A (PCLA) segments.…”
Section: Synthesis Of P[(cla)-co-(clo)] and P[(cla)-co-(vlo)] Copolymersmentioning
confidence: 99%
“…As potential compatibilizing agents in polyamides/PCL blends, lactam‐CL block copolymers were prepared through reactive extrusion as well 66, 67. Continuous copolymerization of CL with ε‐ caprolactam (CLa) and ω ‐lauryl lactam (LLa) were carried out in a modular intermeshing co‐rotating twin‐screw extruder.…”
Section: Reactive Extrusion (Co)polymerization Of Cyclic (Di)estersmentioning
confidence: 99%
“…Therefore, in order to produce environmental friendly materials, poly( ε ‐caprolactone) (PCL), and various types of biodegradable plastics have been developed 19–21. Several researchers have successfully prepared PCL by ring‐opening polymerization by reactive extrusion 22–28. Only a few studies describing PCL‐containing copolymer synthesis by reactive extrusion have been reported 29–31.…”
Section: Introductionmentioning
confidence: 99%